Epsitemologi Penafsiran Musdah Mulia Tentang Homoseksual - Nur Rofiah; Abdul Muid Nawawi; Ahmad Royhan Firdausy (Institut PTIQ Jakarta, 2019)
The homosexual controversy not only shook the principles in Islam, but also the principles of religion besides Islam, especially Christians and Jews. Allegedly, the culture that became the background of each religion was similar, giving birth to a similar shock. Therefore, even though orthodoxy, homosexuality is considered complete, the controversy about this is still pulsing. One thinker who is trying to find a new perspective on homosexuality is Musdah Mulia. This study is about to unravel Musdah Mulia’s epistemology in developing his arguments about homosexuality and how Musdah Mulia interpreted the verses of the Al-Quran relating to homosexuality